2020
DOI: 10.1088/1757-899x/937/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Case study: Solar electric vehicles in India.

Abstract: Over exploitation of fossils fuel to meet humans luxurious in present day life has created imbalance in the ecosystem so to have a balance “Green revolution” is required. It means that there is need of using renewable energy resources instead of non-renewable energy which do not harm the environment and also does not contribute in increasing carbon footprint. In context to this each and every sector in the world is adopting alternative resources (renewable energy) to reduce somehow the degradation of environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…In future, research can be conducted with actual electric car owners. Prajapati et al (2020) suggested in his case study related to solar vehicles that is, solar tricycles, solar e‐rickshaws, solar cars, and solar vans. This study suggested that solar electric vehicles can be the future for India and rest of world.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In future, research can be conducted with actual electric car owners. Prajapati et al (2020) suggested in his case study related to solar vehicles that is, solar tricycles, solar e‐rickshaws, solar cars, and solar vans. This study suggested that solar electric vehicles can be the future for India and rest of world.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In further studies other factors can also be included like; safety, interest, perceived consumer effectiveness, experience, risk, information. In future, research can be conducted with actual electric car owners Prajapati et al (2020). suggested in his case study related to solar vehicles that is, solar tricycles, solar e-rickshaws, solar cars, and solar vans.…”
mentioning
confidence: 99%
“…Kendaraan listrik ini tidak mengeluarkan emisi gas buang sebagaimana yang terjadi pada kendaraan konvensional yang menggunakan Bahan Bakar Minyak (BBM). Sejak tahun 2008 terjadi kebangkitan dalam produksi kendaraan listrik, hal ini akibat adanya inovasi teknologi baterai dan komitmen negaranegara di dunia untuk mengurangi emisi gas rumah kaca yang menyebabkan global warming [7][8][9]. Salah satu tipe kendaraan listrik yang sekarang berkembang pesat adalah sepeda listrik (Electric Bicycle).…”
Section: Pendahuluanunclassified